Entrepreneurship and Industrial Organization: A Review and Research Agenda - Prijanka, Mariska (AIBPM Publisher, 2023)
Industrial organization and entrepreneurship can be closely associated subjects, as both require an understanding of the structure and behavior of firms within an industry. This paper aims to review the literature connecting industrial organization and entrepreneurship to develop a better understanding and propose a research agenda. It provides insights into the emergence, development, and conceptual synthesis of industrial organization and entrepreneurship-related issues for future research. The findings reveal that entrepreneurship can be correlated with industrial organization primarily through entry, innovation, and competition. This connection seeks to understand how new firms emerge and grow within existing industries and how incumbents can adapt and compete with new entrants. Entrepreneurship also plays a crucial role in facilitating market entry which can also foster increased innovation and competition. The recognition that entrepreneurship can stimulate entry, innovation, and competition underscores its critical role in shaping market dynamics. This highlights the need for interdisciplinary research, where scholars and policymakers can collaborate to gain a more holistic understanding of market dynamics and promote economic growth.